Amplifying and Reversing the Chiral Bias in Asymmetric Photo‐Polymerization Reaction - Dingdong Liu; Xiangxiang Xu; Zeyu Feng; Chutian Zhang; Jialei Li; Yifan Xie; Jingguo Li; Hongli Zhang; Gang Zou (Advanced Science)
Abstract Circularly polarized light (CPL) is inherently chiral and is regarded as one possible source for the origin of homochirality. Coincidentally, chiral metal nanoparticles have great prospects in asymmetric photochemical reactions since they can enhance the chiral light‐matter interactions. Nonetheless, little is known about how the spin angular momentum of light competes with the chiral electromagnetic field in the vicinity of a chiral nanoparticle during the chiral induction and amplification process. Here, an asymmetric photo‐polymerization system is presented where the chiral bias can be selectively regulated by the combination of chiral fields CPL and Ag nanoparticles, either constructively or destructively. Synergistic chiral amplification effect is observed when the handedness of both are matched, while the opposite‐handed CPL can overrule the polymer helicity during the chain propagation process when the chiral near‐field is weak. There is a bifurcation point in the chiral bias for the orthogonal control of the polymer helicity during the asymmetric photo‐polymerization process, favoring for programmable chiroptical micropatterns and multi‐channel independent information encoding. This work not only highlights opportunities for selectively regulating the asymmetric photopolymerization but also is highly valuable for fundamental understanding of the symmetry breaking in photochemical reactions.